Programma: 13 februari: Bad Livers, Macavity's Cat; 20 februari: Somebody's Brother, The Saw Doctors (1993)
Programma: 13 februari: Bad Livers, Macavity's Cat; 20 februari: Somebody's Brother, The Saw Doctors.